Fulfilling the Promise of Technology Transfer : Fostering Innovation for the Benefit of Society. - Hishida, Koichi. (Springer Japan, 2013)
This book offers ideas and case studies promoting innovation by universities and research institutes worldwide, covering the R&D value chain, licensing, income generation, start-ups and entrepreneurship, and new roles for universities in fostering innovation.